Effect of probiotic Bioplus 2B on growth performance and carcass composition of rainbow trout, Oncorhynchus mykiss (Walbaum, 1792) larvae - Alizadeh, Moreza; Farzanfar, Ali; Bahabadi, Mahmood Nafisi (Indian Journal of Fisheries, 2012)
The objectives of the present study were to evaluate some factors such as growth performance, survival rates, food conversionratio (FCR), protein efficiency ratio (PER), specific growth rate (SGR), net protein utilization (NPU) and nutritionalvalues of rainbow trout (Oncorhynchus mykiss) larvae, fed on pellets incorporated with a commercial probiotic â€œBioPlus2Bâ€. This product contains two stains of bacteria viz., Bacilus subtilis and Bacillus licheniformis. For experimental feeding,12,000 numbers of rainbow trout larvae having mean weight of 400 mg were held in 12 Californian troughs as six treatmentswith two replications at a density of 1000 nos. per trough. Fish were fed with probiotic supplemented (at 0, 0.1, 0.2, 0.50.75 and 1% levels) pellet diets for a period of 36 days. The results showed that there was significant correlation betweenincreasing rate of probiotics fed and some parameters like weight gain (WG), growth rate (GR), SGR and NPU in theexperimental treatments. On termination of the experimental feeding, it was observed that increasing level of probiotics inthe diet had a direct relation with protein content of the larvae and inverse relationship with lipid value.